Menopausal syndrome: associated symptoms and their mechanisms are the keys to comprehend alternative pathogenic treatment - G.B. Dikke (LCC «Medicine-Inform», 2019)
Menopausal syndrome: associated symptoms and their mechanisms are the keys to comprehend alternative pathogenic treatment G.B. Dikke Academy of Medical Education named F.I. Inozemtsev, St. Petersburg, Russian Federation This article provides pathogenic basis for the effect of non-hormonal medications (i.e., tofisopam and red clover dry extract) to manage menopausal symptoms and evaluates their efficacy by the results of clinical trials. Menopausal symptoms are clearly related with abnormal neurotransmitter production (serotonin and noradrenalin). Therefore, atypical benzodiazepines (e.g., Grandaxin) and/or isoflavones (Feminal) may be effective for the disorders associated with the involution of female reproductive system after menopause. Both agents reduce the rate and severity of hot flashes, anxious depression, and sleep disorders. In addition, Feminal which demonstrates estrogen-like effect improves vaginal and urinary mucosa health and cognitive functions and reduces the severity of metabolic endocrine disorders in postmenopausal women. The algorithm of treatment choice for menopausal syndrome (i.e., monotherapy of combination of non-hormonal medications) was developed. Hence, the data on the efficacy of atypical benzodiazepine, Grandaxin, and isoflavone, Feminal, for menopausal symptoms allow to recommend these agents when menopause hormonal therapy is limited. Key words: menopause, menopausal syndrome, serotonin, noradrenalin, tofisopam, Grandaxin, phytoestrogens, isoflavones, gynestein, Feminal. For citation: Dikke G.B. Menopausal syndrome: associated symptoms and their mechanisms are the keys to comprehend alternative pathogenic treatment. Russian Journal of Woman and Child Health. 2019;2(1):57-64.